Characterization of a Drosophila phosphorylation-dependent nuclear-localization-signal-binding protein. - Cserpán, I (1997)
A 94 kDa nuclear-localization-signal (NLS)-binding protein was purified from Drosophila embryos. The NLS of the simian-virus-40 T-antigen is specifically bound by the dephosphorylated form of the protein. After phosphorylation, the affinity of the protein for the NLS is sharply decreased. In the dephosphorylated form, p94 (protein of 94 kDa) is the major NLS-binding protein in Drosophila embryos. Immunoprecipitation confirmed the ATP-dependent phosphorylation of p94, and co-precipitation of two additional phosphorylated proteins, indicated that the NLS-binding protein is part of a larger complex in Drosophila embryos. In agreement with the immunoprecipitation results, cross-linking experiments demonstrated the interaction of p94 with three additional proteins. These protein-protein interactions were also phosphorylation-dependent.